2019
DOI: 10.2298/vsp170519098v
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary tuberculosis in the immunocompromised patients

Abstract: Background/Aim. During the last few decades, immunocompromising diseases led to an increase in the number of tuberculosis cases. The aim of this study was to examine the influence of immunocompromising diseases on the course of tuberculosis. Methods. The research included two groups, each consisting of 40 subjects with tuberculosis, who were treated at the Institute for Pulmonary Diseases of Vojvodina during 2010 and 2011. The first group had no immunocompromising diseases (the kontrol group), whereas the seco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Since then, many studies have shown T-I-B opacities in various diseases [8,9] although in our setup, the most common cause remains endobronchial spread of tuberculosis. High dose or prolonged continuous use of steroids can cause generalized immunosuppression with increased incidence of TB due to reactivation of latent infection [10,11]. Airway invasive aspergillosis remains an often neglected cause of T-I-B opacities in immunosuppressed patients.…”
Section: Introductionmentioning
confidence: 99%
“…Since then, many studies have shown T-I-B opacities in various diseases [8,9] although in our setup, the most common cause remains endobronchial spread of tuberculosis. High dose or prolonged continuous use of steroids can cause generalized immunosuppression with increased incidence of TB due to reactivation of latent infection [10,11]. Airway invasive aspergillosis remains an often neglected cause of T-I-B opacities in immunosuppressed patients.…”
Section: Introductionmentioning
confidence: 99%